2022
DOI: 10.3389/fgene.2022.828373
|View full text |Cite
|
Sign up to set email alerts
|

The Role of RAB GTPases and Its Potential in Predicting Immunotherapy Response and Prognosis in Colorectal Cancer

Abstract: Background: Colorectal cancer (CRC) is the third most common cancer worldwide, in which aberrant activation of the RAS signaling pathway appears frequently. RAB proteins (RABs) are the largest Ras small GTPases superfamily that regulates intracellular membrane trafficking pathways. The dysregulation of RABs have been found in various diseases including cancers. Compared with other members of Ras families, the roles of RABs in colorectal cancer are less well understood.Methods: We analyzed the differential expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Prior study has shown that high RAB6B expression promoted cell proliferation and the cell cycle G1/S phase transition through AKT/ JNK signaling pathways in gastric cancer (Zhao et al, 2020). By contrast, RAB6B was low expressed in pancreatic and colorectal cancers, and correlated with poorer prognosis in patients (Anand et al, 2020;Jiang et al, 2022). These results suggested that RAB6B may play specific roles in different TME.…”
Section: Discussionmentioning
confidence: 85%
“…Prior study has shown that high RAB6B expression promoted cell proliferation and the cell cycle G1/S phase transition through AKT/ JNK signaling pathways in gastric cancer (Zhao et al, 2020). By contrast, RAB6B was low expressed in pancreatic and colorectal cancers, and correlated with poorer prognosis in patients (Anand et al, 2020;Jiang et al, 2022). These results suggested that RAB6B may play specific roles in different TME.…”
Section: Discussionmentioning
confidence: 85%
“…NARR, an isoform of RAB34, is small GTPases involved in protein transport and is associated with many cancers ( 59 , 60 , 61 , 62 , 63 , 64 ). For example, recent studies have found that RAB34 was downregulated in CRC ( 63 ) but upregulated in the non-small cell lung cancer ( 64 ) when compared with nonmalignant tissues. RAB34 expression is also linked with poor prognosis in CRC ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation demonstrated that Rab10 is a direct target gene of miR-10527-5p. Rab10, a member of the small GTPase family, 40 has been identified as an oncogene in various cancers, such as breast cancer, osteosarcoma, and ESCC, and it participates in tumor metastasis by affecting different processes, including invasion, migration, EMT, immune evasion and chemoresistance. [41][42][43] In our study, Rab10 was found to be significantly elevated in LNM + ESCC tissues and tended to be associated with poor prognosis in ESCC patients.…”
Section: Discussionmentioning
confidence: 99%